Insektisida Nabati Kulit Durian (Durio zibethinus murr) dan Jahe (Zingiber 0fficinale) Untuk Mengendalikan Larva Kumbang Tanduk (Oryctes rhinoceros) Di Laboratorium - Nurhasanah Nurhasanah; Nuraida Nuraida; Iwan Hasrizart (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Al Azhar Medan, 2023)
Durian and Ginger Peel Vegetable Insecticides to Control Horn Beetle Larvae The aim of this study was to determine the effectiveness of the use of durian peel extract and ginger extract to control horn beetle larvae (O. rhinoceros). This research was conducted at the Laboratory of the Faculty of Agriculture, Al-Azhar University. The study used a Completely Randomized Design (CRD) Non Factorial consisting of 3 levels, as follows: D0J0 (Control), D1 (15 ml of durian peel extract L.air-1), D2 (20 ml of durian peel extract L.air-1) , D3 (25 ml durian peel extract L. water-1), J1 (15 ml ginger extract L. water-1), J2 (20 ml ginger extract L. water-1), J3 (25 ml ginger extract L. water -1). Parameters observed were the proportion of mortality of O. rhinoceros larvae and time of initial death (LT50). The results of the study showed that the proportion of mortality of O. rhinoceros larvae to treatment had a significant effect, while the proportion of mortality was significantly different with all treatments. The fastest initial time of death occurred in treatment D3, namely 1,293 HSA in the range 1,248–1,328 HAS.